2018
DOI: 10.1097/pai.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TLE-1 and CD99 in Carcinoma: Pitfalls in Diagnosis of Synovial Sarcoma

Abstract: The characteristic immunoprofile for the diagnosis of synovial sarcoma, a neoplasm of unclear tissue origin, is expression of transducer-like enhancer of split 1 (TLE-1), CD99, partial expression of cytokeratin, and epithelial membrane antigen by immunohistochemistry (IHC). Diagnostic dilemma or misdiagnosis can occur due to overlap in IHC and morphology with carcinomas, and particularly poorly differentiated and metastatic tumors. The frequency of TLE-1 and CD99 expression in carcinomas by IHC has not been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…However, even strong membranous CD99 immunoreactivity is not specific for EwS [28,55]. Indeed, 40% of non-EwS cases examined in the current study (128/320 samples, representing 11 distinct tumor entities) exhibited a strong CD99 immunostaining (IRS >8).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, even strong membranous CD99 immunoreactivity is not specific for EwS [28,55]. Indeed, 40% of non-EwS cases examined in the current study (128/320 samples, representing 11 distinct tumor entities) exhibited a strong CD99 immunostaining (IRS >8).…”
Section: Discussioncontrasting
confidence: 50%
“…For almost three decades, the standard immunohistochemical marker for EwS has been the membranous glycoprotein CD99 [1,26], which shows a striking sensitivity but low specificity for EwS [27][28][29][30][31]. Since fusions of the FET family of genes comprising FUS, EWSR1, and potentially TAF15, with members of the ETS family of transcription factors (including FLI1, ERG, ETV1/4/6 and FEV) are largely pathognomonic for EwS [32][33][34], molecular identification of such fusions is the most reliable diagnostic test for EwS to date [24].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Moreover, non-mesenchymal tumors have recently been shown to overexpress TLE1 by immunohistochemistry, including cutaneous neoplasms (eg, spindle cell melanoma), mesothelioma, and carcinomas. [10][11][12][13][14] As illustrated in the biopsy from our patient, a carcinoid tumor of the lung with spindle cell morphology raises a large differential diagnosis that requires resolution through ancillary studies. Carcinoid tumors of the lung are characterized by various growth patterns (eg, organoid, nested, trabecular) and demonstrate a range of morphologic appearances from epithelioid to oncocytic to spindled, among others.…”
Section: Discussionmentioning
confidence: 89%
“…The high sensitivity and specificity are due to the predominance of epithelial and lymphoid tumours at this site, and their diagnosis as malignant usually does not represent a problem; however, mesenchymal lesions are considerably more difficult to classify [6]. Previous studies in the literature have shown that diagnostic accuracy of FNA is 63-95% for mesenchymal lesions [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In our cohort, high diagnostic accuracy of 93.8% was observed in differentiating benign neoplasm from malignancies on cytomorphology.…”
Section: Discussionmentioning
confidence: 99%